MANIFESTAREA LOCULUI DE CONTROL DIN PERSPECTIVA CONSTRUCTIVĂ ÎN PSIHOLOGIA CONTEMPORANĂ - USM ADMIN (Moldova State University, 2012)
The investigation of locus of control represents a growing interest today in the psychology of control. Trying to place the control analysis from the perspective of personal construct is supported by theories that are based on an optimistic future-oriented design and subjective perception of control.